Decolonising Media Accessibility: Alternative Approaches to Media Access for Film and Live Events - Dangerfield, Kate; Moores, Zoe; Romero Fresco, Pablo (Journal of Audiovisual Translation, 2024)
In this article, we explore the different forms that accessibility can take, both in theory and in practice, focusing on filmmaking and live events. We question the role and responsibility that we, as humans, have in determining how collaboration and participation can be successful within the research process, in bringing creativity and difference to the content that is created, and in challenging biases and discriminatory practices. We situate this discussion within broader societal debates: we question the balance of ideology and art and explore how questions of justice lie behind the access that is provided. We weave together the voices of three academics and use our discussions to reflect on where theoretical notions meet as we face the reality of trying to embed translation and access in the creative projects we are involved in. By exploring case studies of accessible filmmaking and practical considerations around how access can be implemented at the live events that showcase them, we try to illustrate the different forms that access can take and how we can continue to build a notion of more generative access, by welcoming in new approaches and perspectives and using them to create a more equitable and inclusive society. Lay summary In this article, we explore how films and live events can be made more accessible. We discuss ideas we might have about doing this, and what actually happens when we try to do it. As humans, we play an important role in making sure that people can take part, as we explore ideas, create films that are creative and different, and as we challenge unfair practices. As we do this, we must make sure that each stage of what we are doing is as accessible as possible. At the same time, we ask some important questions: how well do our ideas meet artistic practice? How does access relate to justice? We three academic researchers, try to answer these questions together as we explore the terms that we use and the ideas we hold. We also explore some of the challenges we have faced as we tried to make sure the projects we worked on were accessible. We talk about some of these projects to show how access can vary and to share our idea of what access can look like if we try new things. What we really want to do is to use access to create a more welcoming society, which everyone can be a part of.